The Involvement of the Chemokine RANTES in Regulating Luminal Acidification in Rat Epididymis - Feng, Xiao; Ma, Bin-Fang; Liu, Bo; Ding, Peng; Wei, Jin-Hua; Cheng, Pang; Li, Sheng-Yu; Chen, Dong-Xu; Sun, Zhi-Jian; Li, Zhen (Frontiers in Immunology, 2020)
Background A complex interplay between different cell types in the epithelium leads to activation of the luminal acidifying capacity of the epididymis, a process that is crucial for sperm maturation and storage. Basal cells sense the luminal angiotensin II (ANG II) and stimulate proton secretion in clear cells through nitric oxide (NO). Our previous study has shown the chemokine regulated upon activation normal T-cell expressed and secreted (RANTES) was expressed in the F4/80 positive macrophages of human epididymis. The objective of this study was to explore the involvement of RANTES in regulating the luminal acidification in the rat epididymis. Methods The role of RANTES was investigated by in vivo perfusion with recombinant RANTES, Met-RANTES, and PBS of different pH values. Furthermore, rats vasectomy was performed to alter the epididymal luminal pH. RIA was used to measure the tissue homogenate ANG II concentration. Real time-PCR and western blot were employed to examine the expression levels of AGTR2, RANTES, CCR1, CCR5, and iNOS in epididymis. Results RANTES was restricted to the basal macrophages of epididymal ducts and co-localized with its receptors CCR1 and CCR5. Both V-ATPase and iNOS were up-regulated in the cauda epididymis after perfused with recombinant RANTES, while the antagonist Met-RANTES perfusion led to a complete abrogation of the increased expression of V-ATPase in the apical membrane of clear cells and iNOS in macrophages. Upon alkaline perfusion, RANTES expression was significantly increased and the apical accumulation of V-ATPase in the clear cells was induced in the cauda epididymis. The luminal pH in the cauda epididymis increased after vasectomy. The concentration of the ANG II and the expression levels of AGTR2, RANTES, CCR1, CCR5, and iNOS dropped in the cauda epididymis following vasectomy. Conclusion Upon the activation of basal cells, RANTES might induce the NO release from macrophages by interacting with its receptors, which increases proton secretion by adjacent clear cells. Thus, RANTES is possible to participate in the crosstalk among basal cells, macrophages and clear cells for the fine control of an optimum acidic luminal environment that is critical for male fertility.